(untitled) (Journal of Education and Development, 2022)
Taking W Middle School for example, this paper is aimed to explore the effect of teachers’ questioning upon junior high school students’ English classroom activity. Classroom observation, questionnaire and face-to-face interview are employed as the research method. The results show that classroom questioning can be divided into display questions and referential questions in English teaching. Besides, the easier questions are, the more active students are, so it’s interesting to find out all the students interviewed by the writer said they prefer to answer questions of appropriate difficulty. In addition, most students prefer open questions according to the data from questionnaires. What’s more, there are many factors leading to low activity and negative classroom atmosphere is the main factor.